Isozyme analysis of philippine cashew (Anacardium occidentale L.) germplasm - Maranan, Faith Santiago (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2008)
Sixteen accessions of cashew (Anacardium occidentale L.) collected and maintained by the National Plant Genetics Resources Laboratory, Institute of Plant Breeding, Crop Science Cluster, College of Agriculture, University of the Philippines Los Banos were subjected to isozyme analysis. Two zones of activity were noted for alkaline phosphatase {ALP-1 and ALP-2), acid phosphatase (ACP-1 and ACP-2), esterase {EST-1 and EST-2), shikimate dehydrogenase (SKDH-1 and SKDH-2), isocitrate dehydrogenase (IDH-1 and IDH-2), phosphoglucomutase (PGM-1 and PGM-2) and 6-phosphogluconate dehydrogenase (PGD-1 and PGD-2). Twelve of the loci were monomorphic and homozygous recessive for the S allele. The gene frequency of the twelve recessive alleles was 1.0. Only two presumptive loci, ACP-2 and EST-2, were found to be polymorphic. NTSYSpc-version 2.11s by SAHN was used to construct a dendrogram based on the presence and absence of bands. Using a similarity index coefficient of 0.93, three major clusters were observed. Cluster I was made up of 11 accessions, nine of which came from Zambales and one each from Palawan and Los Banos. Cluster II consisted of only three accessions, two from Palawan and one from Zambales. Cluster III was observed to contain two accessions both from Zambales. The clustering together of accessions from Zambales, Palawan and Los Banos would indicate genotypic similarity among cashew accessions considered.